Физико-математическое моделирование сложных элементов акробатического рок-н-ролла - Адашевский, Владимир Михайлович; Ермаков, С. С.; Фирсова, Ю. Ю.; Adashevskiy, V. M.; Iermakov, S. S.; Firsova, Iu. Iu. (Харьковская государственная академия дизайна и искусств, 2013)
Показаны направления биомеханического обоснования выполнения элемента акробатического рок-н-ролла Фус–сальто с учётом конкретных физических данных спортсменов. Разработана математическая модель для определения влияния на качество выполнения технического элемента таких параметров как: скорость и угол вылета центра масс тела спортсмена, положение центра масс тела спортсмена в начальных фазах бросковых упражнений, начальная угловая скорость вращения тела спортсмена. Определены параметры влияния осевых моментов инерции при различных группировках тела на угловую скорость вращения тела спортсмена в полете и сил сопротивления воздушной среды на характеристики полёта тела. Показаны направления выбора необходимых биомеханических характеристик, которые способны реализовать спортсмены. Предложены рекомендации по повышению эффективности выполнения элемента акробатического рок-н-ролла Фус–сальто.

It is shown directions of biomechanics substantiation of implementation acrobatic rock-and-roll Fussalto element taking into account concrete physical data of sportsmen. Mathematical model is developed for determination the influence on a quality of implementation of technical element of such parameters as: speed and angle of flight of centre-of-mass sportsman’s body, position of centre-of-mass body of sportsman in the initial phases of throw exercises, initial angular velocity of rotation of body of sportsman. It is developed mathematical model to determine the impact on the quality of the technical element parameters such as speed and angle of flight of centre-of-mass of the athlete’s body, the position of center-of-mass of the athlete’s body in the initial phases of throwing exercises in the initial angular velocity of the athlete’s body. The parameters of exposure axial moments of inertia for different groupings of body angular velocity the athlete’s body in flight and air resistance forces of environment to flight characteristics of the body. Directions of choice of necessary biomechanics descriptions which are able to realize sportsmen are shown. It is offered recommendations are on the increase of efficiency of implementation of element of acrobatic rock-and-roll of Fus-salto
Physical mathematical modelling of difficult elements of acrobatic rock-and-roll
Keywords: биомеханика; траектория; бросок; biomechanics; trajectory; throw